Efficient Text Message Hidden Technique Using YIQ Model - Ali Nasser Hussain; Entidhar Mhawes Zghair (Journal of Madenat Alelem University College, 2017)
This paper produces and investigates the steganography technique of information hiding in communication system by using other information to provide major security. Nowadays, the security in the information transferring plays a vital role due to data protection importance. Therefore, the traditional techniques by using invisible ink or hidden tattoos need to developed and compensate under digital processing. Hence, Red (R), Green (G) and Blue (B) plans (RGB) approach is activated to improve the proposed scheme. By this technique, the text message converted to binary code as first stage. Then, the binary code is arranged as an image and converted to (YIQ) model as second stage. The final stage is to save the picture and converted to color image to minimize the distortion. Results show high Peak Signal to Noise Ratio (PSNR) and minimum Mean Square Error (MSE) in the extracted picture. The suggested algorithm is a promising technique to enhance the current and future communication security and open new widow to develop this issue.